(untitled) - Wright, Reg (Đồng Nai, 2009)
Richard Walton is in trouble again. He has lost his job, and he has borrowed money from his sister, Jennifer - again. And now he has disappeared. Jennifer is looking for him, and so are the police. They both have some questions that they want to ask him. How did he lose his job? Why did he fly to Frankfurt? Who gave his girlfriend those very expensive gold ear-rings? Only Richard can answer these questions. But nobody can find Richard.
Keywords: English language,Ngôn ngữ tiếng Anh,Short stories,Truyện ngắn,England literature; Readers,Người thích đọc sách